-30=-6(5+p)

Simple and best practice solution for -30=-6(5+p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -30=-6(5+p) equation:


Simplifying
-30 = -6(5 + p)
-30 = (5 * -6 + p * -6)
-30 = (-30 + -6p)

Add '30' to each side of the equation.
-30 + 30 = -30 + 30 + -6p

Combine like terms: -30 + 30 = 0
0 = -30 + 30 + -6p

Combine like terms: -30 + 30 = 0
0 = 0 + -6p
0 = -6p

Solving
0 = -6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6p' to each side of the equation.
0 + 6p = -6p + 6p
Remove the zero:
6p = -6p + 6p

Combine like terms: -6p + 6p = 0
6p = 0

Divide each side by '6'.
p = 0

Simplifying
p = 0

See similar equations:

| 6x+15=3y-3 | | -3(-x)-7=1+x | | 28=f-3 | | 6000=4 | | 6(p-8)=-42 | | -30+(150)=X | | 24=2(-x+3) | | 2(3y+4+2)= | | 17+10x-3=-3(x-6) | | 14x+8+10x+28=180 | | 9x+5=12x-19 | | 6-(-7+x)=42 | | 600=2x+3y | | -6(5n+5)=-120 | | 8x-27=4x+33 | | 140=90+m | | 12-4x=-5x+22 | | 12x^2+26x-10=0 | | 2(g+4)+5g-1= | | 3n+28=200 | | 0.75n+1.29=7.00 | | x(2x-5)(x^2-3)(5x^3-8)=0 | | -3x=-5x+22 | | 5x-31=2x+5 | | 7x-36=4x+5 | | 5y-[2(y+1)+2]=7z | | (4.6-8n)0.5=3.8 | | 4n-25=75 | | 2(4-x)+7x=13 | | 4x+4=7x-17 | | x+5.5y=x+y+81 | | 4(5a+16)=16(a-35) |

Equations solver categories